(untitled) (Journal of Universal Science Research, 2025)
This article explores the structural and semantic characteristics of exotic plant names in English and Uzbek languages. It analyzes how such names are formed, the linguistic and cultural factors influencing their usage, and the degree of borrowings and adaptations in both languages. The research highlights similarities and differences in morphological structures, metaphoric meanings, and etymological origins of exotic plant terms, contributing to a better understanding of cross-cultural linguistic representation of flora.